Arahan Pengembangan Kawasan Industri Kota Sorong Berbasis Green Industry - Dewi, Yashinta Kumala; Hehanussa, David; Akil, Arifuddin (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2019)
Sorong is a city that has been planned as an economic center that will serve Eastern Indonesia. This makes Sorong City planned as a Special Economic Zone (SEZ) based on the national spatial plan. The development that occurred in Indonesia is more dependent on economic aspects without looking at other aspects so that the need for industrial estate planning that not only involves economic aspects, but involves social aspects and environmental aspects. The purpose of this plan are: 1) know the current location of industrial estate in terms of the principles of green industry; 2) evaluate the principles of green industry, especially in determining the location; 3) draw up direction for the development of the industrial area of shoves based on the principles of green industry. This research uses scoring method, spatial analysis, and conceptual analysis. this study found that based on the principle of green industrial location, the application of these principles had a total application of 75.6% and on the principle of sustainable site, the area of land was classified as